Electrochemical oxidation of recycled carbon fibers for an improved interaction toward alkali-activated composites. (25th September 2022) - Li, Huanyu; Liebscher, Marco; Yang, Jian; Davoodabadi, Maliheh; Li, Lihui; Du, Yuhang; Yang, Bin; Hempel, Simone; Mechtcherine, Viktor
Abstract: In this study, recycled carbon fibers (rCF) obtained from pyrolysis are utilized as reinforcements in fly ash-GGBS alkali-activated composites. Since the bond between the fiber and matrix is relatively poor, anodic oxidation was conducted by applying various voltages to enhance the interfacial interactions. Cyclic voltammetry (CV) was performed to investigate the chemical reaction process during the electrochemical fiber modification. Scanning electron microscopy showed the removal of contaminations and impurities from the fiber surfaces by anodization. Thermogravimetric analysis (TGA) analysis was performed to compare the heat resistance properties of the CF reinforced composites and single-fiber tension tests were carried out to evaluate the influence of the electrochemical treatment on the fiber's properties. Single fiber pullout tests and energy dispersive X-ray mapping indicated a remarkable improvement of compatibility between the modified fibers and the matrix, since chemical bonds are formed between oxygen-related functional groups from the anodized fiber surfaces and the alkali-activated matrix. With the addition of 1 wt.% rCFs compressive and flexural strengths have been enhanced by up to 25% and 19%, respectively, compared to the plain composites. The results reveal that electrochemical surface treatment of rCFs is beneficial for enhancing the flexural behavior of rCF-reinforced composite owing to enhanced interfacial bonding. However, this method also provokes a slight increase of porosity compared with untreated fiber-reinforced samples, as proved by mercury intrusion porosimetry (MIP). This study provides a promising utilization of rCF in the production of waste-based fiber-reinforced alkali-activated composites, promoting the management of carbon fiber-reinforced plastic waste. Graphical abstract: Image 1 Highlights: Recycled carbon fibers are the first time modified by electrochemical oxidation. The fiber-matrix interaction was significantly improved. Proper conditions can be selected to avoid severe loss of fiber strength. The treatment changed hydration products and microstructures of composite.